PENGARUH VARIASI POSISI PEMASANGAN DAN ARAH ALIRAN FLUIDA TERHADAP KINERJA VENTURI VAKUM - R. N. Akhsanu Takwim; Kris Witono (Universitas Lambung Mangkurat, 2019)
A liquid fluid flow that is driven by a centrifugal pump past the ventury channel needed to produce the vacuum conditions at the ventury vacuum pump. The amount of vacuum pressure produced by ventury is influenced by the increase of flow rate due to the channel cross section that follows the Bernoulli principle. The flow rate on the channel is affected by the discharge generated by the pump that follows the law of continuity. In addition to speed, the pressure of channel input is also a variable that affects ventury vacuum pressure. Pressure losses and flow discharge caused by the connection or turn of the pipe arising from the installation design, will affect the performance of the Setrifugal pump in the form of discharge flow and pressure that ultimately strongly affects the rally Venturi vacuum work. Therefore, it is necessary to evaluate the influence of the design of the istalation associated with the position of ventury mounting and the direction of the flow to the pressure and discharge of the vacuum to be the primary purpose of this research so that the variables are obtained The performance of a ventury vacuum pump. In this research the placement of vacuum ventury in several positions, namely vertical position, horizontal position and tilt position 45o. Then measured parameters are occurring, such as discharge fluid flow, liquid fluid pressure and vacuum pressure occurring on the pipe. From this study obtained optimum performance on the installation with a sloping ventury position of 45o with the direction of the downward flow, which resulted in the lowest vacuum pressure of-65 CmHg with ventury suction flow of 33.01 liters/minute.